I've got you under my skin: inflammatory response to elephant seal's lice - Leonardi, María Soledad; Krmpotic, Cecilia Mariana; Barbeito, Claudio Gustavo; Soto, Florencia Anabella; Loza, Cleopatra Mara; Vera, Ricardo Bruno; Negrete, Javier (Medical and Veterinary Entomology)
Seals (Phocidae) undergo an annual cycle of moulting that implies hair regeneration, and in the case of southern elephant seals, it also involves the superficial strata of the epidermis. Therefore, surviving the moulting period is crucial for their obligate and permanent ectoparasites. Throughout evolutionary time, sucking lice (Echinophtiriidae) have developed morphological, behavioural and ecological adaptations to cope with the amphibious lifestyle of their hosts. Lepidophthirus macrorhini, the Southern elephant seal louse species, faces the additional challenge of surviving attached to the host during the moulting period. Since lice live on the skin, L. macrorhini has developed a unique survival strategy by piercing the skin of their host, thus keeping them protected from moulting. During fieldwork in Patagonia and Antarctica, skin samples with lice within were collected for histological analysis to assess whether these parasites caused damage to the host. Lice generate an inflammatory process in the host's dermis, and these lesions could alter the normal chemical and mechanical protective properties of the skin facilitating secondary infections. Further studies that analyse the potential pathogens in those skin lesions are necessary to properly assess the real impact of ectoparasites on their host health. Fil: Leonardi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Krmpotic, Cecilia Mariana. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Morfología Evolutiva y Desarrollo; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Barbeito, Claudio Gustavo. Universidad Nacional de La Plata. Facultad de Ciencias ...